Topical treatment of ointment containing ethanol extract of Archidendron pauciflorum fruit peel on the wound healing in streptozotocin-induced diabetic mice - DESAK MADE MALINI; MADIHAH MADIHAH; FITRI KAMILAWATI; NINING RATNINGSIH; KARTIAWATI ALIPIN; JOHAN ISKANDAR (Smujo International, 2017)
Malini DM, Madihah, Kamilawati F, Ratningsih N, Alipin K, Iskandar J. 2017. Topical treatment of ointment containing ethanol extract of Archidendron pauciflorum fruit peel on the wound healing in streptozotocin-induced diabetic mice. Nusantara Bioscience 9: 306-311. Diabetic wounds lead to severe tissue damage and are difficult to cure. One alternative medicine known well by local Indonesian communities to treat diabetic wounds is the fruit peel of djengkol. This study aimed to evaluate the ointment containing ethanol extract of djengkol fruit peel to accelerate wound healing process in the skin of streptozotocin-induced diabetic mice. The method was experimental using completely randomized design with six treatments and four replications. Diabetes was induced by intraperitoneal injection of streptozotocin 180 mg/kg BW. Mice with blood glucose level ≥150 mg/dL were used for diabetic mice models. The incision wound created at dorsolateral region of shaven skin at ±1 cm2 using sterile scissors. The ointment containing extract was applied topically to the diabetic mice wounds at concentration of 5%, 10% and 15%, as well as Betadine® as the reference group. The ointment basis was applied to the wound of diabetic mice as a positive control and to the wound of non-diabetic mice as a negative control. The treatment was done twice a day for 14 days. The results showed that topical application of ointment containing ethanol extract of djengkol fruit peel at concentration of 10% gave significant recovery (p<0.05) on the wounded skin by the enhancement of re-epithelization and granulation tissue, as well as the increase of capillary number and collagen density which were higher than other treatments and comparable to negative control group. It was concluded that the topical application of ointment containing ethanol extract of djengkol fruit peel can support the healing of diabetic wounds.